Current Ethical Issues in Polish HRM - Ryan, Leo V. (Journal of business ethics, 2006)
Contemporary HRM was introduced into Poland by the arrival of international corporations with their professional systems of Human Resource Management, which emphasizes ethical personnel management. This research is based on data collected from a questionnaire and interview of 40 women and men professional graduates of the 2004 Weekend MBA Program at Poznan University of Economics eliciting their perceptions of ethical issues in Polish HRM. The present Polish economic situation, with 19% unemployment, precipitates many ethical challenges. The questionnaire and interviews resulted in 217 observations and specific examples of ethical HRM issues. Examples fall in two broad categories and five specific Human Resource areas. The broad external categories are: (1) History and cultural attitudes and (2) Exploitation of the current unemployment situation. Historical and cultural attitudes influence attitudes toward work; company discipline; property and ownership; law and social expectations at work. The history of personnel departments in Socialistic Poland explains many of these attitudes. The five specific categories are: (1) Ethical issues in recruitment; (2) Ethical issues in hiring (Discrimination issues); (3) Ethical issues in performance appraisals and promotions; (4) Abuse of authority (including sexual harassment), and (5) “Mobbing”. Ethical issues in these categories include correlation with appropriate Polish Labor and Penal Laws. This research reveals some HRM ethical challenges unique to Polish HRM. The research emphasizes professional HRM and ethical expectations, which are now being recognized and accepted as a strategic component of Polish management